1972
DOI: 10.1111/j.1365-2362.1972.tb00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Response to Thyrotoxicosis and Hypothyroidism in Human Liver and Muscle: Comparative Aspects*

Abstract: Abstract. 1. Activities of phosphoglucomutase, hexokinase, glucose‐6‐phosphate dehydrogenase, triosephosphate dehydrogenase, mitochondrial glycerophosphate dehydrogenase, hexosediphosphatase and phosphoenolpyruvate‐carboxykinase, of enzymes involved in the citric acid cycle and connected pathways, of hydroxyacyl‐CoA dehydrogenase and carnitine acetyltransferase were determined in biopsy specimens of liver and of tibialis anterior muscle from thyrotoxic and hypothyroid patients and from controls. The results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…There was little or no rise in muscle oxidative capacity in guinea pigs and a decrease in rabbits after excess thyroid hormone administration (33). The very limited information available in man was obtained in small cross-sectional comparisons of hyperthyroid and euthyroid human subjects (36,37). These studies reported conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…There was little or no rise in muscle oxidative capacity in guinea pigs and a decrease in rabbits after excess thyroid hormone administration (33). The very limited information available in man was obtained in small cross-sectional comparisons of hyperthyroid and euthyroid human subjects (36,37). These studies reported conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect generally seems to have been given little atten tion. Thus, in some papers the mere mention of 'healthy control subjects' is made without further details (7,10,11). The present subjects were -when one considers the purpose of this investigation -practically healthy since they had neither any muscle disease, nor a dimin In spite of the somewhat higher values found here, citrate synthase belongs to those enzymes having a comparatively low activity in human skeletal muscle.…”
Section: Discussionmentioning
confidence: 80%
“…ished functional activity of the corresponding muscles until a few days before surgery. On the other hand, the comparatively larger group studied certainly offers more information than data from six or three subjects (3,11). In a recent publication, Bass et al (4) described higher values of citrate synthase activity in the m. vastus lateralis quadricipitis of sport-practic ing subjects (9.2 ± 0.83 U/g) and of highperformance athletes (14.8 ± 0.56 U/g wet weight, 25 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only sparse information is available on enzyme activities in human skeletal muscles [6,18,37,41,42,46,48]. Moreover, the determinations are from different muscles and from biopsies taken with different techniques which may influence the level of activity.…”
Section: Discussionmentioning
confidence: 99%